Protection for Women Migrant Workers: The Delaying Legal Reform - Irianto, Sulistyowati (Yayasan Jurnal Perempuan, 2020)
Seen as a breakthrough in protecting migrant workers, of whom are predominantly female, Law No. 18/2017 on the Protection of Indonesian Migrant Workers (The Migrant Workers Act of 2017), replacing Law No. 39/2004, is not void of imperfections. Prima facie, the act may be seen as progressive development in protecting Indonesian migrant workers, having embraced the many experiences and realities their profession entails. However, upon investigating the Act under the careful lens of Feminist Jurisprudence as well as other national legal instruments for gender equality, the Migrant Workers Act of 2017 still provides unsatisfactory details in regardsto the protection of female workers; if the government does not quickly act by making corresponding regulations, the Act will in fact, introduce us to new problems from what was seen as a one-size fits all solution. In its implementation, legal literacy becomes one ofthe most profound challenges the 2017 Act faces. Field research findings in three areas (Sukabumi, Lampung, and Jakarta) show that legal literacy on this Act remains sparse. This article will address problems in regards to the 2017 Act, its implementation, and solutionsto develop more tangible legal instruments in protecting Indonesian migrant workers, in particular, women, who, in foreign lands, often face the risk of violence and abuse on a daily basis with little to no protection.Â Â